Inter-Annual Variability of Organic Carbon Concentration in the Eastern Fram Strait During Summer (2009–2017) - Engel, Anja; Bracher, Astrid; Dinter, Tilman; Endres, Sonja; Grosse, Julia; Metfies, Katja; Peeken, Ilka; Piontek, Judith; Salter, Ian; Nöthig, Eva-Maria (Frontiers in Marine Science, 2019)
The Arctic Ocean plays a key role in regulating the global climate, while being highly sensitive to climate change. Temperature in the Arctic increases faster than the global average causing a loss of multiyear sea-ice, and affecting marine ecosystem structure and functioning. As a result, Arctic primary production and biogeochemical cycling are changing. Here, we investigated inter-annual changes in the concentrations of particulate and dissolved organic carbon (POC, DOC) together with biological drivers, such as phyto- and bacterioplankton abundance in the Fram Strait, the Atlantic gateway to the Central Arctic Ocean. Data have been collected in summer at the Long-Term Ecological Research observatory HAUSGARTEN during eight cruises from 2009 to 2017. Our results suggest that the dynamic physical system of the Fram Strait induces strong heterogeneity of the ecosystem that displays considerable intra-seasonal as well as inter-annual variability. Over the observational period, DOC concentrations were significant negatively related to temperature and salinity suggesting that outflow of Central Arctic waters carrying a high DOC load is the main control of DOC concentration in this region. POC concentration was not linked to temperature or salinity but tightly related to phytoplankton biomass as estimated from chlorophyll-a concentrations (Chl-a). For the years 2009-2017 no temporal trends in the depth-integrated (0-100m) amounts of DOC and Chl-a were observed. In contrast, depth-integrated (0-100m) amounts of POC as well as the ratio [POC]:[TOC] decreased significantly over time. This suggests a higher partitioning of organic carbon into the dissolved phase. Potential causes and consequences of the observed changes in organic carbon stocks for food-web structure and CO2 sequestration are discussed.